Functional insights of nucleocytoplasmic transport in plants - Tamura, Kentaro; Hara-Nishimura, Ikuko (Frontiers in Plant Science, 2014)
Plant nucleocytoplasmic transport beyond the nuclear envelope is important not only for basic cellular functions but also for growth, development, hormonal signalling, and responses to environmental stimuli. Key components of this transport system include nuclear transport receptors and nucleoporins. The functional and physical interactions between receptors and the nuclear pore in the nuclear membrane are indispensable for nucleocytoplasmic transport. Recently, several groups have reported various plant mutants that are deficient in factors involved in nucleocytoplasmic transport. Here, we summarise the current state of knowledge about nucleocytoplasmic transport in plants, and we review the plant-specific regulation and roles of this process in plants.